Evaluation of different anesthetic agents in dogs - Kilic, S; Isler, CT (Indian Veterinary Journal, 2005)
Care in selection of an agent for safe anesthetic management is essential, since it always constitutes a threat to the life of the patient (Orkin and Copperman, 1983). Many researchers (Hartman et al., 1,992; Elliott and Strunin, 1993; Kenna and Jones, 1095) have used different anesthetic combinations considering their efficacy and non-toxic effects. Yet, a drug consisting of all positive characteristics of an ideal anesthetic hat not been invented. The purpose of this study was to compare the efficacy of five anesthetic agents used commonly in canines by considering various clinical and hemodynamic parameters.
Keywords: Halothane